Neglected Issues in T Lymphocyte Metabolism: Purine Metabolism and Control of Nuclear Envelope Regulatory Processes. New Insights into Triggering Potential Metabolic Fragilities - Naomi Torchia; Carolina Brescia; Emanuela Chiarella; Salvatore Audia; Francesco Trapasso; Rosario Amato (Immuno)
The metabolism of T-lymphocytes has recently emerged as a pivotal area of investigation, offering insights into the supra-genic modulations that can influence the genetic mechanisms underlying lymphocyte clustering processes. Furthermore, it has become a crucial aspect in understanding lymphocyte plasticity within the immune microenvironment, both in physiological and pathological contexts. T-lymphocyte metabolism has recently emerged as a pivotal factor in both targeted therapy and the genetic signature of the T-lymphocyte, as a result of its influence on gatekeeper processes. From this perspective, the interconnections between the metabolic processes traditionally associated with energy production and the capacity to influence the genetic fate of the T lymphocyte have identified purine metabolism and nuclear/cytoplasmic signaling as pivotal elements in comprehending the intricacies of these molecular phenomena. The two aspects of purine metabolism and metabolic/molecular control of the nuclear envelope have been the subject of a number of significant studies published in recent years. However, from a certain perspective, the existing evidence remains sparse and inconclusive, hindering a comprehensive understanding of the subject matter. In this review, we endeavor to establish a connection between these aspects for the first time and to present a review of the molecular, immunological and genetic events that determine how these aspects, which have hitherto received insufficient attention, may represent a new avenue for lymphocyte reprogramming in the therapeutic field. This will be achieved by understanding the connections between nuclear control and purine flux within and outside the cell.